5‐Fluorouracil sensitivity varies among oral micro‐organisms. Issue 8 (August 2016) - Vanlancker, Eline; Vanhoecke, Barbara; Smet, Rozel; Props, Ruben; Van de Wiele, Tom
Abstract : N/A: 5‐Fluorouracil (5‐FU), a commonly used chemotherapeutic agent, often causes oral mucositis, an inflammation and ulceration of the oral mucosa. Micro‐organisms in the oral cavity are thought to play an important role in the aggravation and severity of mucositis, but the mechanisms behind this remain unclear. Although 5‐FU has been shown to elicit antibacterial effects at high concentrations (>100 μM), its antibacterial effect at physiologically relevant concentrations in the oral cavity is unknown. This study reports the effect of different concentrations of 5‐FU (range 0.1‐50 μM) on the growth and viability of bacterial monocultures that are present in the oral cavity and the possible role in the activity of dihydropyrimidine dehydrogenase (DPD), an enzyme involved in 5‐FU resistance. Our data showed a differential sensitivity among the tested oral species towards physiological concentrations of 5‐FU. Klebsiella oxytoca, Streptococcus salivarius, Streptococcus mitis, Streptococcus oralis, Pseudomonas aeruginosa and Lactobacillus salivarius appeared to be highly resistant to all tested concentrations. In contrast, Lactobacillus oris, Lactobacillus plantarum, Streptococcus pyogenes, Fusobacterium nucleatum and Neisseria mucosa showed a significant reduction in growth and viability starting from very low concentrations (0.2‐3.1 μM). We can also provide evidence that DPD is not involved in the 5‐FU resistance of the selected species. The observed variability in response to physiological 5‐FU concentrations may explain why certain microbiota lead to a community dysbiosis and/or an overgrowth of certain resistant micro‐organisms in the oral cavity following cancer treatment.